Assessing the ultimate strength of damaged tankers: Collision impacts and design improvements - Mahmoud Darwish; Yehia Abdel-Nasser; Yasser M. Ahmed (Alexandria Engineering Journal, 2025)
Tankers transport substantial volumes of oil and other liquid cargoes across extensive distances. Collisions and groundings can inflict significant damage on their hulls, compromise their structural integrity, and raise concerns about environmental catastrophes. When a tanker sustains damage from collision or grounding, its capacity to withstand stress is diminished. Ultimate strength analysis is a critical methodology for assessing the residual strength of a vessel's hull after damage especially those above 150 m in length. This study investigates the influence of key design parameters, namely plate thickness, stiffener type, and material strain rate, on the ultimate bending moment capacity of damaged tanker hull structures. The research employs finite element analysis using LS-Dyna to simulate a perpendicular collision scenario, incorporating detailed representations of the hull structure and material properties. The analysis focuses on assessing the residual strength of the hull after damage by comparing the ultimate bending moment capacity before and after the collision. The research aims to identify effective strategies for mitigating the reduction in ultimate bending moment capacity, such as plate thickness, selecting appropriate stiffener profiles, and leveraging the enhanced properties of high-strain-rate materials. The study explores the potential benefits of utilizing high-strain-rate materials like A572 or 4140 steel to enhance the structural resilience of tankers. The findings of this research have significant implications for improving the safety and operational efficiency of tanker vessels by enhancing their structural robustness and potentially reducing repair costs and downtime. Future research should further investigate the impact of these parameters on other critical failure modes, such as buckling and shear, and explore the feasibility and cost-effectiveness of implementing high-strain-rate materials in large-scale tanker construction.